Nanomaterials-Mediated Immunomodulation for Cancer Therapeutics - Jindal, Ajita; Sarkar, Sounik; Alam, Aftab (Frontiers in Chemistry, 2021)
Immunotherapy holds great promise in overcoming the limitations of conventional regimens for cancer therapeutics. There is growing interest among researchers and clinicians to develop novel immune-strategies for cancer diagnosis and treatment with better specificity and lesser adversity. Immunomodulation-based cancer therapies are rapidly emerging as an alternative approach that employs the host’s own defense mechanisms to recognize and selectively eliminate cancerous cells. Recent advances in nanotechnology have pioneered a revolution in the field of cancer therapy. Several nanomaterials (NMs) have been utilized to surmount the challenges of conventional anti-cancer treatments like cytotoxic chemotherapy, radiation, and surgery. NMs offer a plethora of exceptional features such as a large surface area to volume ratio, effective loading, and controlled release of active drugs, tunable dimensions, and high stability. Moreover, they also possess the inherent property of interacting with living cells and altering the immune responses. However, the interaction between NMs and the immune system can give rise to unanticipated adverse reactions such as inflammation, necrosis, and hypersensitivity. Therefore, to ensure a successful and safe clinical application of immunomodulatory nanomaterials, it is imperative to acquire in-depth knowledge and a clear understanding of the complex nature of the interactions between NMs and the immune system. This review is aimed at providing an overview of the recent developments, achievements, and challenges in the application of immunomodulatory nanomaterials (iNMs) for cancer therapeutics with a focus on elucidating the mechanisms involved in the interplay between NMs and the host’s immune system.